Abundancia y estructura poblacional de dos recursos pesqueros bentónicos fuera y dentro del área de una concesión marítima portuaria en Caldera, Región de Atacama, Chile - Vega, JM Alonso; Valdebenito, Marcelo; Caillaux, Luis; Bravo, Jorge (Revista de Biología Marina y Oceanografía, 2019)
This study compares density and size structure of kelp Lessonia berteroana and sea urchins Loxechinus albus inside and outside a port concession area in Caldera. Greater abundance and larger adult individuals in populations of both benthic resources in this zone preliminarily indicates that this might be replicating a marine protected area. In the future, this port concession could contribute to the conservation of benthic resources as a reference site, without access to fisheries, useful for validating or implementing measures and actions in management plans or other instruments to support conservation.